2021
DOI: 10.1021/acsaem.0c03255
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of PbSe Nanocomposites from Solution-Processed Building Blocks

Abstract: High thermoelectric performance and low material cost are essential to the commercialization of thermoelectric modules. Microstructural design, size effects, and rational band engineering are among the keys to high thermoelectric performance, especially for nanocomposites. Here, we demonstrate a facile and versatile bottom-up approach to produce nanocomposites by heat consolidating solution-processed PbSe nanoparticles with a proper amount of Ag. In this PbSe-Ag system, a certain amount of Ag diffuses into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…As seen in Figure b, the clear peaks of Cu 2p exhibited two peaks at 952.5 and 932.7 eV, originating from Cu 2p 1/2 and Cu 2p 3/2 of Cu + , respectively. , The spectrum of the Ge 2p exhibited two peaks at 1220.6 and 1218.8 eV in Figure c, which were indexed to 2p 3/2 of Ge 4+ in the sample . The two peaks at 55.3 and 54.0 eV in the Se 3d spectrum as seen in Figure d were attributed to Se 3d 3/2 , which was related to the Se 2– . , As illustrated in Figure e, we found that the high-resolution Bi 4f spectrum displayed two peaks at 166.2 and 160.8 eV, which were assigned to Bi 4f 5/2 and Bi 4f 7/2 of Bi 3+ , respectively . While two distinct peaks situated at 163.4 and 158.2 eV were identified as Bi 4f 5/2 and Bi 4f 7/2 of Bi 3+ , severally, exhibiting the presence of Bi 3+ in the sample.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…As seen in Figure b, the clear peaks of Cu 2p exhibited two peaks at 952.5 and 932.7 eV, originating from Cu 2p 1/2 and Cu 2p 3/2 of Cu + , respectively. , The spectrum of the Ge 2p exhibited two peaks at 1220.6 and 1218.8 eV in Figure c, which were indexed to 2p 3/2 of Ge 4+ in the sample . The two peaks at 55.3 and 54.0 eV in the Se 3d spectrum as seen in Figure d were attributed to Se 3d 3/2 , which was related to the Se 2– . , As illustrated in Figure e, we found that the high-resolution Bi 4f spectrum displayed two peaks at 166.2 and 160.8 eV, which were assigned to Bi 4f 5/2 and Bi 4f 7/2 of Bi 3+ , respectively . While two distinct peaks situated at 163.4 and 158.2 eV were identified as Bi 4f 5/2 and Bi 4f 7/2 of Bi 3+ , severally, exhibiting the presence of Bi 3+ in the sample.…”
Section: Resultsmentioning
confidence: 84%
“…25 The two peaks at 55.3 and 54.0 eV in the Se 3d spectrum as seen in Figure 4d were attributed to Se 3d 3/2 , which was related to the Se 2− . 24,26 As illustrated in Figure 4e, we found that the high-resolution Bi 4f spectrum displayed two peaks at 166.2 and 160.8 eV, which were assigned to Bi 4f 5/2 and Bi 4f 7/2 of Bi 3+ , respectively. 27 While two distinct peaks situated at 163.4 and 158.2 eV were identified as Bi 4f 5/2 and Bi 4f 7/2 of Bi 3+ , 27 severally, exhibiting the presence of Bi 3+ in the sample.…”
Section: Phase Composition Ofmentioning
confidence: 80%
“…As illustrated in Figure 12, we further summarize the future outlooks in the field of conducting polymerbased TE materials and devices [219][220][221][222][223] .…”
Section: Conclusion Challenges and Outlookmentioning
confidence: 99%
“…To tune the band structure of p -type PbSe, many different dopants have been examined, such as by substituting Cu/Sr/Ba/K/Ag for Pb or Te/Cl for Se [ 16 , 17 , 18 , 19 ]. In addition, the doping method has also been explored [ 20 , 21 ]. Compared with other processes, the flux method is widely considered to obtain highly crystallized and phase-pure samples [ 22 ].…”
Section: Introductionmentioning
confidence: 99%